2019
DOI: 10.1155/2019/8013851
|View full text |Cite
|
Sign up to set email alerts
|

A Fractal Approach for Predicting Unsaturated Hydraulic Conductivity of Deformable Clay

Abstract: The relative hydraulic conductivity is one of the key parameters for unsaturated soils in numerous fields of geotechnical engineering. The quantitative description of its variation law is of significant theoretical and technical values. Parameters in a classical hydraulic conductivity model are generally complex; it is difficult to apply these parameters to predict and estimate the relative hydraulic conductivity under deformation condition. Based on the fractal theory, a simple method is presented in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…10.1680/jgeot.19.p.058 Chen et al, 2019;Tao et al, 2019). Unsaturated permeability also can be determined using empirical formulations, macroscopic models, or statistical models involving SWRCs (Leong and Rahardjo, 1997;Patil and Singh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…10.1680/jgeot.19.p.058 Chen et al, 2019;Tao et al, 2019). Unsaturated permeability also can be determined using empirical formulations, macroscopic models, or statistical models involving SWRCs (Leong and Rahardjo, 1997;Patil and Singh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to use simple mapping method to predict the permeability coefficient of unsaturated soil. Tao and Zhu [25] derive a fractal model of the relative permeability coefficient of unsaturated soil based on fractal theory and seepage theory. The expression is as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this paper recommends first measuring the unsaturated relative permeability coefficient and SWCC of the soil before deformation and fitting the value of λ based on the measured data before deformation, that is the λ value after deformation. This paper takes the Touchet silt loam in the literature [23] as an example to compare and analyze the difference between the prediction method proposed by Tao and Zhu [25], and the predicted results are shown in Figure 7. As illustrated in Figure 7, the predicted values of the unsaturated relative permeability coefficient obtained using the simplified unified model are better to those obtained using the Tao and Zhu model and are more in line with the measured value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the expansion and contraction of soils will have a significant impact on the soil water retention curve (e.g., Chen, Chen, & Yang, 2020;Romero, Della Vecchia, & Jommi, 2011). Many models have also been proposed to describe the soil water retention curve and relative hydraulic conductivity for deformable soils (e.g., Chen et al, 2020;Hu, Chen, Liu, & Zhou, 2013;Huang, Barbour, & Fredlund, 1998;Tao et al, 2019). However, further investigations of the models for the soil water retention curve and relative hydraulic conductivity of deformable soils are beyond the scope of this study.…”
Section: Models For Comparisonmentioning
confidence: 99%